Hubungan Self-Esteem Remaja Awal Dengan Perilaku Kesehatan Gigi dan Mulut (Studi Pada Pelajar SMP di Kecamatan Karangpucung) - Dewi, Noni Anggraeni Permata; Kusuma, Ira A.; Nosartika, Isniya (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
Self-esteem was a psychological aspect that not only affects mental heath, but also has an important contribution to physical health. Self-esteem was thought to be an aspect that affects early adolescents during puberty, impact on health behavior, one of them was oral health behavior. The aim of this research to determine the relationship between early adolescent self-esteem and oral health behavior in junior high school students in Karangpucung DistrictThis was an analytic observational study with a cross-sectional design. The research sample was 315 junior high school students in Karangpucung District with convenience sampling. Instrument in this study used a Rosenberg Self-Esteem Scale (RSES) and oral health behavior questionnaire. The Spearman Rank correlation test used to determine the relationship between early adolescent self-esteem and oral health behavior in junior high school students in Karangpucung District. There was a significant relationship between adolescent self-esteem and oral health behavior toward positive, weak correlation strength (p=0,004, r=0,163). There was a relationship between early adolescent self-esteem and oral health behavior in junior high school students in Karangpucung District, namely students who have high self-esteem characteristics tend to have oral health behavior in the moderate category.